(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Hypertension is a major global health problem and an important risk factor for cardiovascular and renal diseases. Genetic factors, particularly angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism, have been implicated in the pathogenesis of hypertension. The present study aimed to evaluate the association between ACE gene I/D polymorphism and hypertension among the South Indian population. Methodology: A hospital-based case-control observational study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from February 2025 to May 2026. Newly diagnosed hypertensive patients and age- and sex-matched normotensive controls were included after obtaining informed consent. Genomic DNA was extracted from peripheral blood samples and assessed using agarose gel electrophoresis and nanodrop spectrophotometry. ACE gene I/D polymorphism was analyzed using polymerase chain reaction (PCR) technique with specific primers. Genotype frequencies were compared between cases and controls using appropriate statistical analysis. Results: The study demonstrated the presence of II, ID, and DD genotypes among participants. The deletion (D) allele and DD genotype were observed more frequently among hypertensive patients compared to controls, suggesting a positive association with hypertension. Statistical analysis revealed a significant relationship between ACE gene polymorphism and elevated blood pressure. Conclusion: ACE gene I/D polymorphism appears to be associated with hypertension in the South Indian population. The D allele may serve as a potential genetic risk factor for the development of hypertension.